Effects of induction chemotherapy on nutrition status in locally advanced nasopharyngeal carcinoma: a multicentre prospective study. Issue 2 (5th March 2023) - Miao, Jingjing; Wang, Lin; Ong, Enya H.W.; Hu, Chaosu; Lin, Shaojun; Chen, Xiaozhong; Chen, Yuanyuan; Zhong, Yahua; Jin, Feng; Lin, Qin; Lin, Shaomin; Hu, Xuefeng; et al.
Abstract: Background: Induction chemotherapy (IC) and concurrent chemoradiotherapy (CCRT) is the standard of care for locoregionally advanced nasopharyngeal carcinoma (LA‐NPC). This intensive treatment regimen increases acute toxicities, which could negatively impact patients' nutritional status. We conducted this prospective, multicentre trial to investigate the effects of IC and CCRT on nutritional status in LA‐NPC patients, so as to provide evidence for further study of nutritional intervention, which was registered in ClinicalTrials.gov (NCT02575547). Methods: Patients with biopsy‐proven NPC and planned for IC + CCRT were recruited. IC entailed two cycles of 3‐weekly docetaxel 75 mg/m 2 and cisplatin 75 mg/m 2 ; CCRT entailed two to three cycles of 3‐weekly cisplatin 100 mg/m 2 depending on the duration of radiotherapy. Nutritional status and quality of life (QoL) were assessed pre‐IC, post‐cycles one and two of IC, W4 and W7 of CCRT. Primary endpoint was the cumulative proportion of ≥ 5.0% weight loss (WL5.0 ) by the end of treatment (W7‐CCRT). Secondary endpoints included body mass index, NRS2002 and PG‐SGA scores, QoL, hypoalbuminaemia, treatment compliance, acute and late toxicities and survivals. The associations between primary and secondary endpoints were also evaluated. Results: One hundred and seventy‐one patients were enrolled. Median follow‐up was 67.4 (IQR: 64.1–71.2) months. 97.7% (167/171) patients completed two cycles of IC, and 87.7% (150/171) completed at least two cycles of concurrent chemotherapy; all, except one patient (0.6%), completed IMRT. WL was minimal during IC (median of 0.0%), but increased sharply at W4‐CCRT (median of 4.0% [IQR: 0.0–7.0%]) and peaked at W7‐CCRT (median of 8.5% [IQR: 4.1–11.7%]). 71.9% (123/171) of patients recorded a WL5.0 by W7‐CCRT, which was associated with a higher malnutrition risk (NRS2002 ≥ 3 points: 87.7% [WL ≥ 5.0%] vs 58.7% [WL < 5.0%], P  < 0.001) and requirement of nutritional intervention (PG‐SGA ≥ 9 points: 82.0% [WL ≥ 5.0%] vs 66.7% [WL < 5.0%], P  = 0.038). The median %WL at W7‐CCRT was higher in patients who suffered from ≥ G2 mucositis (9.0% vs 6.6%, P  = 0.025) and xerostomia (9.1% vs 6.3%, P  = 0.003). Besides, patients with cumulative WL5.0 also reported a higher detriment on QoL at W7‐CCRT compared with patients without, with a difference of −8.3 points (95% CI [−15.1, −1.4], P  = 0.019). Conclusions: We observed a high prevalence of WL among LA‐NPC patients who were treated with IC + CCRT, which peaked during CCRT, and had a detriment on patients' QoL. Our data support the need to monitor patient's nutritional status during the later phase of treatment with IC + CCRT and inform on nutritional intervention strategies.